“Gemo Ni”: A Grammar Note on Tagabawa Verbs - Marfa, Geoffrey S; Cooke, Mary Jane A (Journal of Social Work and Science Education, 2023)
Tagabawa language’s vitality (bgs) is categorized to be institutional, meaning the language has been developed to the point that it is used and sustained by institutions beyond the home and community. However, the language is still not well documented. Some literature available on the linguistic analysis of Tagabawa is scarce and outdated. There are grammatical descriptions written on Bagobo-Tagabawa; but an updated description is offered by this study as a welcome development to continuous discoveries in the language. Although there is the latest available work on Tagabawa, the Tagabawa-English Dictionary by DuBois in 2016 under the Summer Institute of Linguistics, we believe new literature such as grammatical note would be a great addition to it. To provide further pertinent information in keeping Tagabawa as institutional and well-documented language, this paper documents its variety in Malapangi, Marilog by describing and accounting for its basic linguistic features of Tagabawa language. Furthermore, it provides notes on the salient features of Tagabawa verbs, mainly on its voice, aspects, modes, and transitivity.